Efficacy and safety of pregabalin versus amitriptyline in patients with painful diabetic neuropathy - Daniel, Sujit R.; Badyal, Dinesh K.; Jacob, Jubbin J.; Kaur, Jasleen (International Journal of Advances in Medicine, 2018)
Background: Painful diabetic neuropathy is a common complication of long standing diabetes mellitus. Amitriptyline is commonly used to treat painful diabetic neuropathy. Pregabalin has been shown to be effective in the treatment of painful diabetic neuropathy with lesser adverse effects. Sustained release (SR) of pregabalin has the advantage of once daily dosing and a better patient compliance. Hence, this study was planned to compare the efficacy and safety of pregabalin-SR with amitriptyline in painful diabetic neuropathy. Methods: It is a prospective, open labelled, randomized controlled study. A total of 80 patients diagnosed with painful diabetic neuropathy based on Diabetic neuropathy symptom score and Michigan neuropathy screening instrument, were randomized into two groups to receive amitriptyline and pregabalin SR. Amitriptyline was started at 25mg OD and pregabalin SR 75mg OD for 6 weeks with optional dose titration. Patients were assessed for pain relief by using visual analogue scale and an overall improvement in their general condition by patient’s global impression of change scale. Adverse drug reactions were recorded on each follow up. Results: All patients had significant improvement in pain relief in both the treatment groups. The median VAS (visual analogue scale) score was slightly higher in pregabalin SR group (25 vs 22) however it was not statistically significant. Intergroup comparison did not show any significant differences between the treatment groups. Good and moderate pain relief were noted in 37(92.5%) and 3(7.5%) patients on amitriptyline and 36 (90%) and 4 (10%) patients on pregabalin SR respectively. The common adverse effects reported in amitriptyline group were drowsiness (27.5%) and dry mouth (17.5%) and in pregabalin-SR group were drowsiness (15%) and dizziness (5%). No serious adverse event was reported in either of the groups. Conclusions: In patients with painful diabetic neuropathy both amitriptyline and pregabalin-SR are equally effective in alleviating pain and improving the patient’s general condition, but pregabalin-SR has the advantage of fewer adverse effects and convenient dosage timing.